Change in the humus state of chernozem podzolized after application of organic fertilizers - Tovstyi, Yu.M.; Skrylnyk, Ye.V. (AgroChemistry and Soil Science, 2018)
The study was conducted to determine the effect of the action and aftereffect of organic fertilizers on the basis of litter on the qualitative and quantitative composition of humus in chernozem podzolized heavy loam. To determine the effectiveness of the action and the aftereffect of manure and compost on its basis, the qualitative and quantitative composition of humus uses field, laboratory and mathematical-statistical methods. Certainly, the introduction of manure and compost on its basis contributed to an increase in the content of total carbon. On control (without fertilization), the total carbon content was 1.7%. After the introduction of litter, compost (litter + straw) and compost (litter + husk) at a dose of 10 tons / ha, it is 1.80; 1.83 and 1.90% respectively.